How Should Capital Be Taxed? Theory and Evidence from Sweden - Spencer Bastani; Daniel Waldenström (Institute of Labor Economics (IZA), 2018)
This paper presents a comprehensive analysis of the role of capital taxation in advanced economies with a focus on the Swedish experience. We synthesize the existing theoretical literature, present facts about the capital stock and its distribution, review current capital tax practices and empirical findings regarding their effects on economic activity. The paper also examines the political feasibility of capital taxation by presenting results from a unique attitude survey targeted to a large representative sample of the Swedish population. Finally, we tie together our findings and discuss their implications for tax policy.
Keywords: D31; F38; H21; H24; 330; optimal taxation; capital taxation; wealth tax; inheritance tax; corporate tax; income inequality; wealth inequality; political economy; preferences for redistribution